2019
DOI: 10.1007/s12665-019-8490-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating elastic wave velocities in Brazilian municipal solid waste

Abstract: The sanitary landfills in Brazil are, generally, characterized by their high organic material content (around 60%), presence of different types of mixed wastes, and low compaction energy, which differentiates them from the landfills of developed and high-income countries. To prevent environmental and slope stability risks, it is crucial to understand the behavior of such landfills and the changes in their physical properties over time. The compression wave velocity (V p ) and shear wave velocity (V s ) are imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Atypical high V s observed near the surface were possibly due to cover soil or other stiff material (Zekkos et al 2014 ; Ramaiah and Ramana 2017 ). These trends may explain the relatively low velocities measured at landfills with poor compaction and thin cover soil layer (Abreu et al 2016 ; Aranda et al 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Atypical high V s observed near the surface were possibly due to cover soil or other stiff material (Zekkos et al 2014 ; Ramaiah and Ramana 2017 ). These trends may explain the relatively low velocities measured at landfills with poor compaction and thin cover soil layer (Abreu et al 2016 ; Aranda et al 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the previous studies, V s value has been reported ≈83-220 ms −1 for Cozzo Vuturo landfill, Italy (Castelli et al, 2017) and 70-200 ms −1 for different landfills in southeast Michigan such as Arbor Hills Oakland Heights landfill, Carleton Farms landfill and Sauk Trail Hills landfills (Zekkos et al, 2014). Aranda et al (2019) have compiled results of shear wave velocity of MSW in landfills available in the literature and reported that V s varies widely from 50 to 400 ms −1 . However, for the landfill at City of Campinas in São Paulo State, Brazil, the V s value (=86-89 ms −1 ) is found to be lower, which is attributed to the less compaction, high OM in MSW and extreme climatic conditions (viz.…”
Section: Compaction During Landfillingmentioning
confidence: 99%
“…However, for the landfill at City of Campinas in São Paulo State, Brazil, the V s value (=86-89 ms −1 ) is found to be lower, which is attributed to the less compaction, high OM in MSW and extreme climatic conditions (viz. high pluviometry index and high temperature) (Aranda et al, 2019). Furthermore, a comparison of the literature data (Anbazhagan et al, 2016;Haker et al, 1997;Zekkos et al, 2014) (refer to Supplemental Table S3) has been conducted as depicted in Figure 11(b), and it can be observed that in general V s tends to increase with depth.…”
Section: Compaction During Landfillingmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, cities modify the heat flow and, consequently, water evaporation processes and rain patterns. Equally important, various urban activities transfer immense amounts of matter from the atmosphere (Babinski et al 2003(Babinski et al , 2012 and from the surface to the soil (CETESB 2013, Santos Filho et al 2017, Aranda et al 2019, rivers (Porto 2003, Xu et al 2019, and aquifers (Foster and Hirata 1988, DAEE 2012, Cary et al 2013, Conicelli 2014, Petelet-Giraud et al 2018, sometimes contaminating them. In this urban cycle of water, energy, and matter, one of the rarely researched components is the aquifer (Foster et al 2011, Hibbs and Sharp 2012, Hirata and Suhogusoff 2019, even in countries in Europe and North America.…”
Section: Introductionmentioning
confidence: 99%